The multi-period service territory design problem – An introduction, a model and a heuristic approach. (December 2016) - Bender, Matthias; Meyer, Anne; Kalcsics, Jörg; Nickel, Stefan
Highlights: A real-world multi-period territory design problem is presented. The scheduling subproblem is formally defined as a mixed integer program (MIP). A heuristic based on a location-allocation scheme is developed. Experiments on real-word instances show the effectiveness of the proposed method. Abstract: In service territory design applications, a field service workforce is responsible for providing recurring services at their customers' sites. We introduce the associated planning problem, which consists of two subproblems: In the partitioning subproblem, customers must be grouped into service territories. In the scheduling subproblem, customer visits must be scheduled throughout the multi-period planning horizon. The emphasis of this paper is put on the scheduling subproblem. We propose a mixed integer programming model for this subproblem and present a location-allocation heuristic. The results of extensive experiments on real-world instances show that the proposed heuristic produces high-quality solutions.